Aggregation induced non-emissive-to-emissive switching of molecular platinum clusters. Issue 13 (20th March 2019) - George, Anu; Maman, Manju P.; Bhattacharyya, Kalishankar; Das Chakraborty, Sudeshna; S, Anjusree; Das, Bikas C.; Senapati, Dulal; Datta, Ayan; Mandal, Sukhendu
Abstract : The aggregation-induced emission mechanism and solvatochromic impact of Pt-SG clusters were studied and the possible applications utilizing these properties are demonstrated. Abstract : We show here for the first time the Aggregation Induced Emission (AIE) mechanism and solvatochromic impact on Pt-SG (SG-deprotonated glutathione) nanoclusters. In this work, the AIE properties of Pt-SG clusters were investigated through computational and spectroscopic investigations. Computational data established that aggregation triggers a distinct change in the frontier molecular orbitals (FMOs) from metal d-orbital centered FMOs in the monomer to metal–thiolate and thiolate centered FMOs in the dimer improving the radiative decay process. Solvent dependent photoluminescence studies proved that a Lewis-acidic environment can significantly perturb the metal-thiolate and thiolate centered FMOs that are involved in the electronic transitions as predicted by our computational work. These semiconducting clusters exhibit a large Stokes shift and zero spectral overlap between absorption and emission which makes this Pt-SG cluster an excellent material for solar concentrators and solid-state light emitters. This AIE-OFF–ON emission was utilized to delineate a proof-of-concept sensor device that is sensitive to temperature and an acid/base.